Efeitos da cetamina sobre comportamentos defensivos em ratos Wistar - Felício, Hadassa Kéuly (Universidade Federal de São Carlos, 2022)
Ketamine is a non-competitive glutamatergic receptor antagonist widely used as a dissociative anesthetic. Preclinical and clinical studies have indicated that ketamine exhibits antidepressant-like effects. Concurrently, much evidence has suggested that glutamatergic neurotransmission may participate in the underlying biological mechanisms of stress responses and anxiety disorders. Thus, it is plausible that ketamine, in addition to its antidepressant-like effects, may also have anxiolytic-like and/or panicolytic-like effects. The present study aimed to investigate the behavioral effects induced by subanesthetic doses of ketamine in rats exposed to the elevated plus-maze (EPM), elevated T-maze (ETM), conditioned place preference/aversion, and catalepsy tests. For that, 145 male Wistar rats weighing on average 340 g were used. For each test, the subjects were randomly allocated into four groups: 1- Saline (0.9% physiological saline), 2- Ket10 (10 mg/kg ketamine), 3- Ket20 (20 mg/kg ketamine) and 4- Ket30 (30 mg/kg ketamine). In the EPM, the dose of 10 mg/kg ketamine decreased the number of entries and the time spent in the open arms, without affecting entries into the closed arms, suggesting an anxiogenic-like effect. No other significant effect of ketamine was observed in the ETM, conditioned place preference/aversion, or catalepsy tests. Although the rapid and sustained antidepressant-like effects of ketamine appear to be a robust finding in the literature, anxiolytic-like and panicolytic-like effects were not observed in the present study. The diversity of results observed for ketamine in animal models for anxiety and panic indicates the need for further investigation.
Ketamine effects on defensive behaviors in Wistar rats
Keywords: Medo; Ansiedade; Labirinto em Cruz Elevado; Preferência/aversão condicionada ao lugar; Catalepsia; Fear; Anxiety; Elevated plus maze; Elevated T maze; Conditioned place preference/aversion; Catalepsy; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL